KAJIAN KERUSAKAN LINGKUNGAN PADA PERAIRAN SUNGAI BEDOG AKIBAT PEMBUANGAN LIMBAH BATIK DI KABUPATEN BANTUL - Pramudya Bagas Utama; Shafira Fitriyani (Hexagon Jurnal Teknik dan Sains, 2022)
Water is one of basic needs of living things on earth. River water utilization in Wijirejo Village, Bantul District is used to rice field irrigation and also as a recipient of liquid waste from batik home industry. River water pollution is indicated by colors and odors which is contained in Bedog River that damage geophysical- chemical and socio-economic environment. This study aims to discover river water and under ground water characteristic, spread of waste, under ground water and river water vulnerability with water pollution management as a control. Research data collection using observation and mapping method. Sample quality under ground water and river water using purposive sampling method. Water quality data using laboratory test and quantitive analysis with pollution index. Determination of under ground water pollution vulnerability level using method PCSM (Point Count System Model). Liquid waste of batik home industry which affects river water quality is indicated by Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) that exceed standard quality those decreasing water quality status before the waste outlet with good condition and at waste outlet is lightly polluted